2004
DOI: 10.1002/chin.200425195
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ligands Related to the O‐Specific Polysaccharides of Shigella flexneri Serotype 2a and Shigella flexneri Serotype 5a. Part 10. Blockwise Approach to Fragments of the O‐Specific Polysaccharide of Shigella flexneri Serotype 2a: Convergent Synthesis of a Decasaccharide Representative of a Dimer of the Branched Repeating Unit.

Abstract: Branched Repeating Unit. -(BELOT, F.; WRIGHT, K.; COSTACHEL, C.; PHALIPON, A.; MULARD*, L. A.; J. Org. Chem. 69 (2004) 4, 1060-1074; Unite Chim. Org., Inst. Pasteur, F-75724 Paris, Fr.; Eng.) -Jannicke 25-195

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The ␤EC disaccharide (16), which has a non-natural EC glycosidic linkage, was synthesized to probe the influence of such linkage on Ab recognition. Since, based on available building blocks, they were considered to be the easiest chemically accessible longer fragments, the octa-B(E)CDAЈBЈ(E)ЈCЈ (20) and decasaccharide DЉAB(E)CDAЈ BЈ(E)ЈCЈ (21) were synthesized to study the length-dependent oligosaccharide-Ab recognition. Љ indicates the residue linked at the nonreducing end (left end), whereas Ј indicates the residue linked at the reducing end (right end) of the AB(E)CD biological RU.…”
Section: Synthetic Oligosaccharides Representative Of S Flexneri 2a mentioning
confidence: 99%
“…The ␤EC disaccharide (16), which has a non-natural EC glycosidic linkage, was synthesized to probe the influence of such linkage on Ab recognition. Since, based on available building blocks, they were considered to be the easiest chemically accessible longer fragments, the octa-B(E)CDAЈBЈ(E)ЈCЈ (20) and decasaccharide DЉAB(E)CDAЈ BЈ(E)ЈCЈ (21) were synthesized to study the length-dependent oligosaccharide-Ab recognition. Љ indicates the residue linked at the nonreducing end (left end), whereas Ј indicates the residue linked at the reducing end (right end) of the AB(E)CD biological RU.…”
Section: Synthetic Oligosaccharides Representative Of S Flexneri 2a mentioning
confidence: 99%
“…Therefore, the crucial LPS detoxification step is avoided. Following the synthesis of a large panel of SF2a O-SP fragments (21)(22)(23)(24)(25)(26) and extensive investigation of their recognition by protective murine monoclonal IgG (mIgG) Abs, we showed that selected synthetic OSs induced an anti-O-SP Ab response in mice, when administered as tetanus toxoid (TT) conjugates. Increasing the length of the carbohydrate hapten from a penta-to a deca-and pentadecasaccharide representing one, two, and three biological RUs of SF2a O-SP (Fig.…”
mentioning
confidence: 99%
“…As an alternative to classical polysaccharide conjugate vaccines, we have developed a strategy based on synthetic carbohydrates that mimic the O-Ag of S. flexneri 2a, including a detailed analysis of the fine specificity of protective antibody/O-Ag recognition. Accordingly, a number of oligosaccharides representative of serotype 2a O-Ag fragments have been synthesized (9)(10)(11). Although several of these were immunogenic in mice when administered as tetanus toxoid conjugates, only certain sequences were able to induce IgG antibodies capable of recognizing the bacterial LPS (12,13).…”
mentioning
confidence: 99%